Towards synergetic combination of traditional and innovative digital teaching and research practices - Olga A. Suleimanova (Peoples' Friendship University of Russia (RUDN University), 2020)
The paper pursues three objectives: to try and define key features of the digital environment which shape modern educational strategies; to specify how they can promote emerging innovative up-to-date teaching/learning practices if combined with conventional teaching; and to analyse the search and research potential of digital engines for teaching/learning and for linguistic research. The methodology the author relied on in the research was to study the portrait of the modern learner and build the educational approach on it which was designed to combine conventional and digital methods. The digital paradigm shapes the educational platforms and introduces dramatic changes into conventional teaching/learning practices to offer a healthy combination. For instance, it makes teachers reconsider the concept of active learning and reshape project-based learning, rendering project activities more practically oriented; or rely on few-shot learning, as this format takes into account the changing cognitive patterns of the millennials who have a shorter focus of concentration. The availability and accessibility of abundant Internet resources has a strong demotivating effect on youngsters' attitude towards hard learning, especially training their ability to memorise and to concentrate. The results of the study and applied approach revealed that students compensated for this by improving their creative potential and higher reactivity, which can be triggered by few-shot learning. Information resources can also contribute to research practices and add to the students' creative approach to research practices which is demonstrated by the sample template offered in the paper.